How Much Do We Know About Drug Handling by SLC and ABC Drug Transporters in Children?. Issue 1 (10th April 2013) - Nigam, S K; Bhatnagar, V
<x xml:space="preserve">Abstract</x> Although solute carrier (SLC) and ATP‐binding cassette (ABC) transporters are critical to the absorption, distribution, and elimination of many small‐molecule drugs in children, how these transporters regulate pediatric drug handling remains unclear. For proper dosing and to diminish toxicity, we need a better understanding of how organ development and functional maturation, as well as developmental changes in systemic physiology, impact transporter‐mediated drug handling at pediatric developmental stages from the preterm infant through adolescence. Clinical Pharmacology & Therapeutics (2013); 94 1, 27–29. doi:10.1038/clpt.2013.82